Contracting: An Entry Point and a Process - Davis, William L.; Borgen, William A. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article outlines an alternative procedure particular for counsellors in junior and secondary schools who often find nondirective techniques to be counterproductive.The authors suggest a two phase contracting system which involves: (a) an overall commitment by the client to participate in counselling combined with a clear offer of service by the counsellor, and (b) small on-going contracts designed to fulfill the overall identified objectives of counselling. Client and counsellor responsibility is outlined for each step in the process. It is concluded that the contracting process provides a meaningful vehicle for counsellors to help adolescent clients clarify and order environmental input so that courses of action can be more meaningfully identified.